Experiences of Māori and Pacific women recruited into a pregnancy clinical trial in Aotearoa, New Zealand: a Kaupapa Māori qualitative study - Matire Harwood; Benjamin B Albert; Rachel Roskvist; Jamie-Lee Rahiri; Richard Enright; Tania Mullane; Vidit Vinod Satokar (BMJ Open, 2025)
Objectives To explore the perspectives of Māori and Pacific women who participated in the Fish Oil study to ascertain what barriers and facilitators may exist for successfully recruiting Māori and Pacific women into clinical trials.Design A Kaupapa Māori qualitative study.Setting Auckland, New Zealand.Participants 16 Māori and Pacific women who participated in the fish oil supplementation during pregnancy study (ACTRN12617001078347p) between 1 January 2017 and 31 December 2020.Main outcome measures Semistructured in-depth interviews were conducted, recorded and transcribed and then subjected to inductive thematic analysis to identify key themes related to barriers and facilitators of successful Māori and Pacific women recruitment into a clinical trial.Results Of 37 eligible Māori and Pacific women who participated in the original Fish Oil study, 16 women consented to participate in this study. Three key themes were identified: (1) relationships matter, (2) privileges and barriers and (3) the study experience. Key facilitators for recruitment included having solid relationships with research team members, practising exemplary professionalism, having clear communication and having the ability to establish rapport and research team flexibility. The desire to create a better future for participants’ babies and to give back to Māori and Pacific communities through participating in a clinical trial were also key drivers of successful recruitment. In contrast, the major barriers described were time pressures and the distance to the research facility.Conclusions Sixteen Māori and Pacific women who participated in a double-blinded randomised controlled trial shared that successful recruitment of Māori and Pacific women into clinical trials can be promoted by research flexibility participants’ whānau/family responsibilities, effective and culturally safe communication, and research teams striving to build and maintain relationships with participants throughout the trial.Trial registeration number Australian New Zealand Clinical Trials Registry, ACTRN12617001078347p. Universal Trial Number (U1111-1199-5860).